Reading, writing and orality at the school from the sociocultural perspective - Galindo-Lozano, Denys Paola; Doria-Correa, Rudy (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper provides the results of a research to describe an approach to language teaching of elementary school teachers, as well as the relationship of this approach to their classroom practices. The qualitative paradigm was assumed, based on the action-research method, where five elementary school teachers from a Colombian educational institution have participated. The results indicate a structuralist conception, from which teachers' teaching practices are guided in the daily exercise of their language classes. This is due to the fact of the detonator of transcription is perceived in writing, graphic representation of the word and memorization in orality. It is concluded that a need to transform the practice of teachers in the area of language towards new teaching scenarios that encourage in-depth analysis of texts and discourses is required, in terms of conditions of production, intentions and effects among language users, in different social and cultural contexts.